WEAR AND CRACK initiation PREDICTION OF RAIL IRREGULARITY WELDING ZONE - WEAR AND; CRACK initiation PREDICTION OF RAIL IRREGULARITY WELDING ZONE (Jixie qiangdu)
In order to investigate the relationship between abrasion and crack initiation in the welded zone of rails and axle weight and friction coefficient， through the field measurement of a large number of uneven weld zones， two kinds of typical weld zone uneven data were fitted， and two kinds of typical uneven wheel-rail contact finite element models of upper convex and lower concave weld zones were established. Combined with the friction work model and Archard wear theory， the maximum wear cross section of the welded zone was predicted， and the crack initiation life of the welded zone was predicted based on the Jiang-Sehitoglu model. It was found that with the increase of axle load， the abrasion rate of both the upper convex and lower concave weld zone increases， and the abrasion rate of the upper convex weld zone increases significantly when the axle load reaches 16 t， while the abrasion rate of the lower concave weld zone increases significantly when the axle load reaches 18 t. The friction coefficient increases from 0.2 to 0.35， and the maximal abrasion amount of the two types of weld zones of the upper convex and the lower concave was 1.93 mm and 1.08 mm， respectively， and the abrasion rate of the upper convex type increased significantly at a friction coefficient of 0.3， while the abrasion rate of the lower concave type increased significantly at a coefficient of 0.35. When the axle load increases from 12 t to 18 t， the service life of the upper convex weld zone decreases less， while the service life of the lower concave weld zone decreases more. In addition， when the friction coefficient was increased from 0.2 to 0.35， its effect on the service life of the upper convex weld zone was significantly smaller than that of the axle load （12~18 t）. However， when the friction coefficient is increased from 0.2 to 0.35， the effect on the service life of the lower concave weld zone is comparable to that of the axle load （12~18 t）.The results show that with the increase of axle load and friction coefficient， the influence of concave irregularity on the life of rail welding zone was more significant. In the process of engineering maintenance， we should pay attention to the appearance of concave welding zone and mark and repair it in time.